Análisis de microdureza de resinas compuestas nanohibridas expuestas al proceso de blanqueamiento con peróxido de hidrogenoal 35%: una revisión sistemática - Viteri Zambrano, Francisco Javier (2025)
Microhardness is an important property of restorative materials in Dentistry, such as nanohybrid composite resins. However, treatments such as tooth whitening with 35% hydrogen peroxide can affect the microhardness of these restorations. Therefore, it is essential to know the effects of whitening on the properties of resins, in the search for the clinical longevity of dental restorations. The objective To analyze the microhardness of nanohybrid composite resins exposed to the whitening process with 35% hydrogen peroxide. Materials and methods: A bibliographic review was carried out, where research will be selected in different databases, such as: LILACS, Scielo, using according to key words of DeCS terminology: microhardness, nanohybrid composite resins, whitening process, 35% hydrogen peroxide. Results: A comprehensive search and analysis of 10 scientific articles selected from 44 main articles was carried out, where 8 of the selected articles confirmed that bleaching with 35% hydrogen peroxide can affect the microhardness and shear bond strength of nanohybrid composite resins. Conclusion: The reviewed studies highlight the importance of evaluating the structural, aesthetic and strength changes in nanohybrid composite resins after bleaching with 35% hydrogen peroxide, and the need to implement appropriate strategies to maintain the quality and durability of dental restorations.